PENGGUNAAN MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA ANAK USIA 5-6 TAHUN DI TK KECAMATAN GUGUK PANJANG KOTA BUKITTINGGI - Mayang Sari; Zulminiati Zulminiati (Early Childhood: Jurnal Pendidikan, 2021)
This research is motivated by the low reading ability, so that it can affect the academic and psychological achievement of children. Psychological problems that arise due to the lack of early childhood reading skills, namely the lack of variety in the media used by the teacher, when doing tasks related to reading children disturb their friends by asking to chat, making noise when their friends are doing assignments, not completing assignments, refusing when asked to do very long tasks, especially tasks that have a lot of reading, difficulty receiving long instructions, not being thorough and rushing when doing assignments. This study aims to determine: the effect of the use of big book media on the reading ability of children aged 5-6 years. This type of research is quantitative. The population in this study amounted to 17 Kindergartens which are kindergartens in the Guguk Panjang District, Bukittinggi City. The samples in this study were seven Kindergartens in Guguk Panjang District, Bukittinggi City. The sampling technique used in this research was cluster sampling (area sampling). Data collection using a questionnaire. Data analysis used descriptive statistics (percentage of results) with the help of SPSS 18.0 for windows. The results of this study indicate that: there is a significant effect on the reading ability of children aged 5-6 years in Kindergarten, Guguk Panjang District, Bukittinggi City, namely the results of the development level of reading ability of children aged 5-6 years who are given treatment after using big book media more higher than before using the big book media.